THE AGREEMENT OF BORROWING MONEY FROM THE VILLAGE OWNED ENTERPRISES (BUMDes) JAYA LESTARI FOR SMALL ENTREPRENEURS KIJANG REJO DISTRICT TAPUNG KAMPAR DISTRICT - Muhammad Ardiansyah; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Village owned enterprises (BUMDes) is form of cooperatives village, but with a name change, so the village-owned enterprises is not much different from the cooperative, which is a business entity consisting of persons or legal entities cooperative with the bases activity based on the principle of cooperation well as people's economic movement based on the principle of kinship. Cooperative aims for the welfare of its members. This research is located in BUMDes Jaya Lestari Jl. Saebani Kijang Rejo village Kec.Tapung Kab.Kampar. The purpose of this study was to determine the lending operations of credit in BUMDes Jaya Lestari and to find out how the settlement when the event of default in BUMDes Jaya Lestari. The method used in this research is the method of sociological research is research on the effectiveness of the law in force or a study of legal identification. In collecting data the author uses methods Interviews, namely data collection tool in the form of question and answer directly between the researcher and the debtor is to conduct interviews with the Chief Director BUMDes Jaya Lestari and has been prepared in advance of equipment used during the interview that the interview guides and study literature, the method collecting data from literature to support the primary data. The results of the authors are their written agreement as evidenced by the Lending Agreement (SP2K), Magnitude Interest Rate on BUMDes Jaya Lestari by 15% - 16% per year. Terms and conditions of lending money at BUMDes Jaya Lestari the authors see the whole field is Kijang Rejo village community and that having Enterprises. Means of dispute resolution when it occurs in BUMDes Jaya sustainable, the reprimand or a warning letter given by the BUMDes Jaya Lestari also sanctions are applied.Keywords : BUMDes, Agreement of borrowing money